2005
DOI: 10.1158/1055-9965.epi-05-0111
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Carcinoma Risks among Menopausal Estrogen plus Progestin and Unopposed Estrogen Users in a Cohort of Postmenopausal Women

Abstract: Background: Because unopposed estrogen substantially increases endometrial carcinoma risk, estrogen plus progestin is one menopausal hormone therapy formulation for women who have not had a hysterectomy. However, endometrial carcinoma risks among estrogen plus progestin users and among former unopposed estrogen users are not firmly established. Methods: We evaluated endometrial carcinoma risks associated with estrogen plus progestin and unopposed estrogen therapies in 30,379 postmenopausal Breast Cancer Detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
74
0
4

Year Published

2007
2007
2012
2012

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 87 publications
(84 citation statements)
references
References 70 publications
6
74
0
4
Order By: Relevance
“…11 Of the 6 studies that were included in the summary estimate, the only study 10 that reported a significantly increased risk allowed for previous unopposed estrogen use, which is a strong endometrial cancer risk factor. Our recent cohort study also reported significantly increased risks associated with sequential regimens, 14 which were defined as progestin taken for <15 days per month but could have included progestin used for <10 days per month. Adding the NIH-AARP findings to the summary estimate reported in the MWS may decrease the magnitude of the association between endometrial cancer and ever-use of sequential regimens that contain !10 days of progestin per cycle.…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…11 Of the 6 studies that were included in the summary estimate, the only study 10 that reported a significantly increased risk allowed for previous unopposed estrogen use, which is a strong endometrial cancer risk factor. Our recent cohort study also reported significantly increased risks associated with sequential regimens, 14 which were defined as progestin taken for <15 days per month but could have included progestin used for <10 days per month. Adding the NIH-AARP findings to the summary estimate reported in the MWS may decrease the magnitude of the association between endometrial cancer and ever-use of sequential regimens that contain !10 days of progestin per cycle.…”
Section: Discussionmentioning
confidence: 92%
“…Other cohort 14 and case-control 7,9,10,12,13,15,21-23 studies have employed variable exposure definitions for estrogen plus progestin. The studies collectively captured different snapshots of the hormone therapy usage patterns that have changed substantially since the middle 1970s.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations